An international survey to identify the intrinsic and extrinsic factors of research studies most likely to change orthopaedic practice. Issue 4 (April 2016) - Thornley, P.; de SA, D.; Evaniew, N.; Farrokhyar, F.; Bhandari, M.; Ghert, M.
Abstract : Objectives: Evidence -based medicine (EBM) is designed to inform clinical decision-making within all medical specialties, including orthopaedic surgery. We recently published a pilot survey of the Canadian Orthopaedic Association (COA) membership and demonstrated that the adoption of EBM principles is variable among Canadian orthopaedic surgeons. The objective of this study was to conduct a broader international survey of orthopaedic surgeons to identify characteristics of research studies perceived as being most influential in informing clinical decision-making. Materials and Methods: A 29-question electronic survey was distributed to the readership of an established orthopaedic journal with international readership. The survey aimed to analyse the influence of both extrinsic (journal quality, investigator profiles, etc.) and intrinsic characteristics (study design, sample size, etc.) of research studies in relation to their influence on practice patterns. Results: A total of 353 surgeons completed the survey. Surgeons achieved consensus on the 'importance' of three key designs on their practices: randomised controlled trials (94%), meta-analyses (75%) and systematic reviews (66%). The vast majority of respondents support the use of current evidence over historical clinical training; however subjective factors such as journal reputation (72%) and investigator profile (68%) continue to influence clinical decision-making strongly. Conclusion: Although intrinsic factors such as study design and sample size have some influence on clinical decision-making, surgeon respondents are equally influenced by extrinsic factors such as investigator reputation and perceived journal quality. Cite this article: Dr M. Ghert. An international survey to identify the intrinsic and extrinsic factors of research studies most likely to change orthopaedic practice. Bone Joint Res 2016;5:130–136. DOI: 10.1302/2046-3758.54.2000578.